A reform of Solfeggio course and application PDCA cycle for music majors at Dalian University - Zhang Lina; Pramote Danpradit (Gemilang Maju Publikasi Ilmiah (GMPI), 2023)
The purpose of the paper is to present the concept of the reform of the Solfeggio course by application PDCA cycle for music majors. Research and teaching tools built with a small group of 26 volunteer students. The PDCA process is used to increase learning management, company management, and instruction enhancement. In order to further progress instructional methodologies and ideas. The Solfeggio course syllabus from 2006 is being rewritten for the 2020 edition. The practicability of the course has also improved, and student enthusiasm for the course has increased in the classroom. General survey outcome found that 90% of students agree that lecturers should raise the quality of teaching, dare to innovate, and increase the attractiveness of the classroom to students. The results indicated that 12.4% of the students are extremely, 77% are somewhat satisfied, 17% are not satisfied, and 9.3% are very dissatisfied.